CERES-Maize Simulation Model: Establishment of Planting Windows for Grains Maize under Rainfed Conditions - H., Abd Razak; B. Y., Aminuddin; R., Mohd Fauzi (Universiti Putra Malaysia Press, 2000)
Growing period or planting windows concepts is a useful approach in identifying suitable planting time for crop under rainfed management. It will help farmers to ensure the crop success. A crop simulation model (CERESMaize model) was used to identify the suitable planting time and maize was used as an indicator crop. The model was validated using compiled data to ensure its fitness within the setup acceptable limit. The model was capable to predict maize yield potential close to the actual yield at the experimental trails but always over estimated at the farm production levels. Under local conditions with favourable soil and climate, the yield potential of maize could be expected greater than 7 t/ha. The yield potentials for most of the zones are relatively low towards the end of year due to a dry period, experienced in most of the crop growing cycle. Based on the yield potential trends, it corresponds to rainfall pattern. In combination with a cut off point at 5 t/ha, its shows most of the zones have double planting windows except for two zones (1 and 26), which have a single planting window. In addition, as example the most suitable planting time within the planting window for zone 9 and 10 were also identified. This information can help farmers in planning their farm in order to have the most efficient operation.